Texture Classification based on First Order Circular and Elliptical Ternary Direction Pattern Matrix - Subba Reddy, K; Vijaya Kumar, V; P. Siva Kumar, A (International Journal of Engineering and Technology, 2018)
Local binary pattern (LBP) captures isotropic structural information and completely fails in representing anisotropic information, however the horizontal elliptical LBP (H-ELBP) and vertical elliptical LBP (V-ELBP) represents partial anisotropic information only. In our earlier work we have derived â€œcircular and elliptical-LBP (CE-LBP)â€ captures both isotropic and anisotropic structural information with a feature vector size equivalent to LBP and it is easy to implement and invariant to monotonic illumination changes. The LBP, local ternary pattern (LTP), CE-LBP and most of the extensions of LBP descriptor basically ignore the directional information. To address this and to capture both isotropic and anisotropic directional information, this paper proposes a â€œcircular and elliptical ternary direction pattern matrix (CE-TDPM)â€. The CE-TDPM encodes the relationship between the central pixel and two of its neighboring pixel located in different angles (Î±, Î²) with different directions. The CE-TDPM evaluated the possible direction variation pattern for central pixel by measuring the first order derivate relationship among the horizontal and vertical neighbors (0o vs. 90o; 90o vs. 180o; 180o vs. 270o; 270o vs. 0o) and derived a unique code. The performance of the proposed method is compared with various other existing methods using the benchmark texture databases viz. Brodtaz, UIUC, Outex and MIT-VisTex. The performance analysis shows the efficiency of the proposed method over the existing methods.Â Â